Illuminating and sculpting the structure and function of mitochondria in sleep-control neurons - Monaco, N (2023)
In Drosophila, sleep deprivation leads to the accumulation of reactive oxygen species (ROS) in the mitochondria of sleep-control neurons projecting to the dorsal fan-shaped body (dFB)(Kempf et al., 2019). ROS levels provide an internal representation of sleep need by activating sleep via the redox-sensitive β-subunit of the voltage-gated potassium channel Shaker (Kempf et al., 2019). Shaker regulates the excitability of sleep-promoting cells via the oxidation state of a stably bound nicotinamide cofactor (Donlea, Pimentel, & Miesenböck, 2014b; Pimentel et al., 2016).